Religion and Science: Analysing Medical Fatwas of the Majelis Ulama Indonesia (2010–2021) - Ali Sodiqin (Journal of Islamic Law)
The advancement of knowledge, particularly in the medical field, often surpasses established religious norms, giving rise to new legal challenges. This presents a significant issue for Islamic scholars and modern institutions such as Majelis Ulama Indonesia (the Indonesian Ulema Council, MUI). This article examines the dialectical relationship between revelation (naṣṣ) and science in the medical fatwas issued by the MUI, focusing on how Islamic scholars construct legal arguments by integrating the Qur’an and Hadith with scientific findings to advance scientific ijtihād (Islamic legal reasoning). Adopting a qualitative, library-based methodology, the study meticulously analyses 20 medical fatwas issued by the MUI between 2010 and 2021. Using a functional interpretive paradigm that incorporates revelation, reason, and reality as foundational elements of fatwa formulation, the article finds that the MUI engages in a dialogical process between revelation and science in its medical fatwas. The dialectic between naṣṣ and scientific discoveries reveals two models of integration: deductive-falsification and inductive-verification. The deductive-falsification model appears in fatwas offering guidance for specific actions, while the inductive-verification model is applied in determining the legal status of scientific products. These integration models demonstrate that the MUI positions naṣṣ as the independent variable and scientific findings as the dependent variable in the development of scientific ijtihād. This approach emphasises the decisive role of revelation in determining the acceptability of scientific advancements as the foundation for legal rulings.